Atsttrin Promotes Cartilage Repair Primarily Through TNFR2-Akt Pathway - Wei, Jianlu; Wang, Kaidi; Hettinghouse, Aubryanna; Liu, Chuanju (Frontiers in Cell and Developmental Biology, 2020)
Background Cartilage defects account for substantial economic and humanistic burdens and pose a significant clinical problem. The efficacy of clinical approaches to cartilage repair is often inadequate, in part, owing to the restricted proliferative capacity of chondrocytes. Molecules have the capacity to promote the differentiation of multipotent mesenchymal stem cells into chondrocytes and may also gain the ability to repair the damaged cartilage. Objective This study aimed to investigate the role of Atsttrin (progranulin-derived engineered protein) in cartilage repair as well as the signaling pathway involved. Methods Primary and mesenchymal stem cell lines were used for the micromass culture. A murine cartilage defect model was used to determine the role of Atsttrin in cartilage repair in vivo. Real-time polymerase chain reaction and Western blot analysis were used to monitor the effect of Atsttrin on the transcriptional and protein levels, respectively, of key anabolic and catabolic signaling molecules. Results Atsttrin stimulated chondrogenesis in vitro and accelerated cartilage repair in vivo. In addition, Atsttrin-mediated cartilage repair occurred primarily through tumor necrosis factor receptor 2-initiated Akt signaling and downstream JunB transcription factor. Conclusion Atsttrin might serve as a promising therapeutic modality for cartilage regeneration.